The new era in Retail: Retail 4.0 centered on the human being and its purchase process - Abreu, Maria José (2019)
In the face of the new "digital phenomenon", a more human-centric and personal-oriented era is predicted. Brands seek to create an emotional bond with the customer and provide an experience that unifies the online and offline world. It was verified that there is a reinforcement of the strategy established in Retail 3.0, continuing with the implementation of the omnichannel business model, but highlighting the consumer and his preferences. This is a very current subject and one that is still the target of many studies, since it is a recent phenomenon and still in application. So, this article allows us to understand the demands that drove the arrival of marketing and Retail 4.0 and what it entails, but that brings with it a central question: "why brands start their activity on the online channel instead of opting for the traditional channel? " It is therefore necessary to understand whether there is a kind of role reversal as to how some brands present themselves to their customers for the first time. If they begin to implement themselves, first, in the digital world, using it as their point of sale (POS), and only then think of integrating a physical store, or if they choose to unify the channels. It was once notable that brands presented themselves to their customers through a physical store and gradually implemented a multi-channel strategy to follow the change in consumer buying behavior, which over the years demonstrated a strong desire to introduce the new technologies in their day-to-day tasks. Nowadays, the reverse is true, that newly created brands even opt to make themselves known in the digital world, some of which later open a physical store or are implemented in multi-brand stores, while others keep only their point of virtual sales. This brings us to some minor issues: why do most brands nowadays start their activity on the online platform and do not follow the physical store? What is the key to success (for a brand to transition from online to offline)? When does a brand feel ready to move to an omnichanel strategy? What resources do they use to understand if the brand is ready for a new step? The objective would be to perceive this new panorama for the brands and that, in the end, it is possible to obtain a set of criteria that allow them to have a greater orientation on this subject.